Repenser les espaces féminins de la ville au regard du genre (al-Andalus, xe-xve siècle) - Christine Mazzoli-Guintard (Genre & Histoire)
For the past thirty years, research about women in al-Andalus, and then in the history of the gender, went further in the knowledge in a field little-explored hitherto. The place of women in the urban world was considered from the perspective of women’s spaces, then the gender gave a new interpretative framework of urban spaces. We offer here an historiographic assessment of the contributions of the gender to our knowledge of the al-Andalus’ cities.